2000
DOI: 10.1089/neu.2000.17.389
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Cerebral Glucose Metabolism and Level of Consciousness During the Period of Metabolic Depression Following Human Traumatic Brain Injury

Abstract: Utilizing [18F]fluorodeoxyglucose positron emission tomography (FDG-PET), we studied the correlation between CMRglc and the level of consciousness within the first month following human traumatic brain injury. Forty-three FDG-PET scans obtained on 42 mild to severely head-injured patients were quantitatively analyzed for the determination of regional cerebral metabolic rate of glucose (CMRglc). Reduction of cerebral glucose utilization, defined as a CMRglc of < or =4.9 mg/100 g/min, was present regionally in 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
128
1
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(139 citation statements)
references
References 35 publications
4
128
1
5
Order By: Relevance
“…Exclusion criteria included the following: (1) terminal illness (e.g., advanced cancer, AIDS); (2) severe previous neurologic disease; and (3) acute complete spinal cord injury. These inclusion and exclusion criteria are consistent with those used for previous publications from the UCLA Brain Injury Research Center (Bergsneider et al, 1997(Bergsneider et al, , 2000Vespa et al, 2003). UCLA's Institutional Review Board approved the protocol, and informed consent was obtained from the patients' legal representatives.…”
Section: Patient Selectionmentioning
confidence: 94%
See 1 more Smart Citation
“…Exclusion criteria included the following: (1) terminal illness (e.g., advanced cancer, AIDS); (2) severe previous neurologic disease; and (3) acute complete spinal cord injury. These inclusion and exclusion criteria are consistent with those used for previous publications from the UCLA Brain Injury Research Center (Bergsneider et al, 1997(Bergsneider et al, , 2000Vespa et al, 2003). UCLA's Institutional Review Board approved the protocol, and informed consent was obtained from the patients' legal representatives.…”
Section: Patient Selectionmentioning
confidence: 94%
“…During this critical postinjury period, there are initially high levels of cerebral glucose consumption, followed by a variable period of normal to mildly depressed glucose metabolism (Bergsneider et al, 1997(Bergsneider et al, , 2000. However, during the same period, many studies have demonstrated a low level of cerebral oxygen consumption relative to the unexpectedly preserved glucose metabolism Jaggi et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the damaged tissue needs more energy for its repair than under physiological conditions, resulting in what has been termed a "flow/metabolism mismatch," a factor that aggravates injury in the traumatic penumbra [62,73]. Furthermore, increased glutamatergic release into the extracellular milieu following injury causes marked increases in glucose use and accumulation of extracellular lactate [53,[74][75][76][77][78][79]. This deregulated cerebral metabolism leads to decreased ATP production causing the failure of ATP-dependent ion channels and proteins leading to ionic osmotic alterations that result in cell swelling and culminating in necrosis [80].…”
Section: Mechanisms Of Neural Injury In the Traumatic Penumbramentioning
confidence: 99%
“…An increasing number of studies on mTBI have focused attention on concussion-induced changes in brain metabolism (Bergsneider et al, 2000;Praticò et al, 2002) including those related to cerebral energy state (Vagnozzi et al, 1999). Hovda and colleagues first suggested the concept of metabolic vulnerability occurring in brain tissue after any concussive episode (Giza & Hovda, 2001;Hovda et al, 1993).…”
Section: Background: Metabolic Changes Characterizing Brain Vulnerabimentioning
confidence: 99%